Production of bio-polyethylene/wood flour biocomposites compatible with PE-g-MA. Assessment of maleic anhydride content in mechanical and thermomechanical properties - Silva, Fabiano Santana da (2021)
The production of ecological materials is being encouraged, aiming to minimize environmental impacts and promote greater sustainability. Therefore, this work aimed to develop bio-polyethylene biocomposites (BioPE)/wood flour (WF), using polyethylene grafted with maleic anhydride (PE-g-MA) as a compatibilizer. The biocomposites were prepared in a corrotational twin screw extruder and injection molded. The properties of Izod impact strength, tensile strength, Shore D hardness, Heat Deflection Temperature (HDT) and water absorption were investigated. Impact strength improved when biocomposite BioPE/WF was made compatible with PE-g-MA. This increase was more expressive for 10% of PE-g-MA with a high degree of maleic anhydride grafting, indicating a higher level of interaction between the phases. The BioPE/WF/PE-g-MA biocomposites showed improved elastic modulus, tensile strength, Shore D and HDT hardness, compared to the non-compatible biocomposite. An important aspect was the reduction of water absorption for biocomposites compatible with PE-g-MA, suggesting a greater barrier effect for the diffusion of moisture. From the point of view of the degree of grafting of maleic anhydride in PE-g-MA, in general, impact strength was the most sensitive property. The results indicate that wood flour is a waste with the potential to be reused in the development of biocomposites.